The Effectiveness of The Word Guessing Game in Improving Vocabulary Mastery of The Fourth-Grade Students at SD Negeri 5 Pagaralam - Nyimas Nur Huda (JEIT (Journal of Educational Innovations and Technologies), 2025)
This study investigated whether there was a significant difference in vocabulary mastery between fourth-grade students at SD Negeri 5 Pagaralam who were taught using the Word Guessing Game and those who were not. It used a quasi-experimental design with pre-test and post-test control groups. Two classes were selected through purposive sampling: IV.C as the experimental group and IV.D as the control group. A multiple-choice vocabulary test was administered before and after treatment. Data were analyzed using paired and independent t-tests. The independent t-test showed a t-obtained value of 4.979, which was higher than the t-table value of 2.009 at a 0.05 significance level. These results indicate that the Word Guessing Game significantly improved students’ vocabulary mastery. Therefore, this game can be considered an effective method for enhancing English vocabulary learning.